Efficacy and Tolerance of Synthetic Cannabidiol for Treatment of Drug Resistant Epilepsy - Klotz, Kerstin A.; Grob, Daniel; Hirsch, Martin; Metternich, Birgitta; Schulze-Bonhage, Andreas; Jacobs, Julia (Frontiers in Neurology, 2019)
Objective: Controlled and open label trials have demonstrated efficacy of cannabidiol for certain epileptic encephalopathies. However, plant derived cannabidiol products have been used almost exclusively. Efficacy of synthetically derived cannabidiol has not been studied before. The objective of this study was to evaluate tolerability and efficacy of synthetic cannabidiol in patients with pharmacoresistant epilepsy. Methods: In this prospective, open-label study (DRKS00013177), patients with pharmacoresistant epilepsy received synthetic cannabidiol in addition to their previously stable anticonvulsive treatment. Starting dose was 5mg/kg/day, up-titrated to a maximum of 50mg/kg/day. Primary efficacy endpoint was monthly frequency of motor seizures at 3 months. Results: Between April 2017 and May 2019, 35 patients were enrolled in the study. Mean age was 19.7 years (SD 14.6). Median motor seizure frequency decreased from 21.8 (IQR 7.5-52.5) seizures per month at baseline to 8.5 (IQR 3.7-28.3, p=0.000) at 3 months, effect not influenced by AED changes and drop-outs. Adjusted percentage reduction was 40.0% (IQR 18.2-58.5). Adverse events (AE) were reported in 25 patients (71.4%), most frequently somnolence (40%), diarrhea (34.3) and loss of appetite (20%). Two patients (5.7%) discontinued treatment due to AE. Median (range) of treatment duration was 321 days (range 36-824). with ongoing treatment up to date in 21 patients (60%). Conclusion: Efficacy and tolerance in our study of synthetic CBD treatment in pharmacoresistant epilepsy is similar to open label studies using plant derived CBD. Regarding economic and ecological aspects, synthetic cannabidiol might be a reasonable alternative to plant derived cannabidiol.